Polyvinyl alcohol/nanocellulose nanocomposites from oil palm empty fruit bunch as anion exchange membranes for direct alcohol-hydrogen peroxide fuel cells - Yunphuttha, Chumphol; Midpanon, Supatta; Marr, David W. M.; Viravathana, Pinsuda (Cellulose (London), 2024)
A series of nanocomposites based on quaternized polyvinyl alcohol (PVA) and nanocellulose (NC) from oil palm empty fruit bunch have been used as anion exchange membranes (AEM) for direct alcohol-hydrogen peroxide fuel cell (DAHPFC) applications. The PVA and NC are individually quaternized with hexadecyltrimethyl ammonium bromide (HDT) and glycidyltrimethyl ammonium chloride (GAC), cross-linked, and cast to form quaternized polyvinyl alcohol/quaternized nanocellulose (QPVA/QNC) membranes following thermal treatment. We observe that an increase of QNC quaternization degree increases quaternary ammonium content and the dimensional stability of the QPVA/QNC membranes while inhibiting PVA matrix crystallinity, decreasing both HDT dispersal and membrane thermal stability. We determine that QPVA/QNC GAC30% membranes exhibit a maximum ion conductivity of 9.85 ± 0.07 mS/cm at room temperature and 29.07 ± 1.76 mS/cm at 80 °C with an ion exchange capacity of approximately 1.14 meq/g. Addition of QNC also enhances the alkaline stability of the optimized QPVA/QNC membrane with less ion conductivity loss. Optimized QPVA/QNC membranes have been demonstrated as an AEM in DAHPFCs without the use of platinum based catalysts. Compared with other membranes, we believe this nanocomposite membrane with comparable performances can promise AEM application in DAHPFCs.